Tribological, corrosion and antibacterial behaviors of Ti-xCu alloy prepared by laser powder bed fusion - X.D. Liang; X.G. Zhang; W.Q. Wang; J.W. Liang; X.H. Zhao; M.Q. Liu; S.Y. Du; Z.H. Zhang (Journal of Materials Research and Technology)
In recent years, the use of laser powder bed fusion (LPBF) technology to produce Ti alloys for medical implants has attracted considerable attention. In this study, Ti-xCu (x = 0, 3, 5, 7 wt%) alloys were prepared using LPBF technology. The results revealed that the addition of Cu into commercial pure titanium (CP–Ti) refined martensitic structure, increased the grain boundary density, reduced the texture strength of CP-Ti on {0001} planes, and enhanced the anisotropy. In addition, the solid solution of Cu in the Ti matrix and the precipitation of the Ti2Cu phase led to solid solution strengthening, precipitation hardening, and grain boundary strengthening, synergistically improving microhardness and tribological properties with increasing Cu content. Meanwhile, long-term immersion electrochemical behavior in simulated saliva fluid, antibacterial, and cytotoxicity experiments on Ti-xCu alloys were conducted. The results indicated that Ti-xCu alloys fabricated by LPBF exhibited favorable corrosion resistance, antibacterial activity, and cell compatibility, thereby presenting significant potential for dental implants.